2017
DOI: 10.1021/acs.biochem.7b00025
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Ferredoxin-Binding Site of a Ferredoxin-Dependent Cyanobacterial Nitrate Reductase

Abstract: An in silico model for the 1:1 ferredoxin (Fd)/nitrate reductase (NR) complex, using the known structure of Synechocystis sp. PCC 6803 Fd and the in silico model of Synechococcus sp. PCC 7942 NR, is used to map the interaction sites that define the interface between Fd and NR. To test the electrostatic interactions predicted by the model complex, five positively charged NR amino acids (Arg43, Arg46, Arg197, Lys201, and Lys614) and a negatively charged amino acid (Glu219) were altered using site-directed mutage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…4a-c), thus is essential for Fd binding. This structural feature is consistent with previous studies showing that Fd features a highly acidic surface, with recruitment usually driven by basic patches on the binding partner [46][47][48] . Furthermore, our surface plasmon resonance (SPR) results demonstrated that the binding affinity of NDH-1L with Fd is significantly increased at higher pH ( Supplementary Fig.…”
Section: Resultssupporting
confidence: 92%
“…4a-c), thus is essential for Fd binding. This structural feature is consistent with previous studies showing that Fd features a highly acidic surface, with recruitment usually driven by basic patches on the binding partner [46][47][48] . Furthermore, our surface plasmon resonance (SPR) results demonstrated that the binding affinity of NDH-1L with Fd is significantly increased at higher pH ( Supplementary Fig.…”
Section: Resultssupporting
confidence: 92%
“…The holoenzyme of the canonical NAS enzymes is hetero-oligomeric in nature, composed of one conserved catalytic subunit and at least one electron transfer subunit (which may be shared with the nitrite reductase) or one electron donor subunit (ferredoxin or flavodoxin) (Fig. 1), wherein the [2Fe-2S] cluster plays a crucial role, universally, in intermolecular electron transfer for nitrate reduction (8,13). In contrast, although the N-terminal region of NasN contains a canonical CA domain, it is NADPH-dependent and lacks the [2Fe-2S] cluster-binding domain.…”
Section: Discussionmentioning
confidence: 99%
“…1), represented by the well-studied enzyme from the terrestrial diazotroph Azotobacter vinelandii (6), directly acquires electrons from flavodoxin via its C-terminal [2Fe-2S] cluster. In contrast, the ferredoxin-dependent heterodimeric NarB (Fd-NarB) acquires electrons from the photosynthetically reduced ferredoxin containing a [2Fe-2S] cluster, as identified in the autotrophic cyanobacterium Synechococcus elongatus (7,8). Thus, the electron donor (flavodoxin or ferredoxin) functions as a subunit of NarB holoenzymes.…”
mentioning
confidence: 99%
See 1 more Smart Citation